TRANSFORMATION OF THE RUSSIAN TAX SYSTEM IN THE CONTEXT OF ESTABLISHMENT OF THE DIGITAL ECONOMY - E. Kirova; N. Morozova; A. Bezverkhiy (Вестник университета, 2019)
The controversial issues of a new approach to solving the problem of transformation of the tax system of the Russian Federation in the context of establishment of the digital economy have been considered. The problems of converting the tax system of the Russian Federation in digital reality and search for approaches to their solution have been identified. The methods of systematic approach, analysis and synthesis, as well as abstraction and generalization have been used. Due to the use of modern business models, carrying- out business activities without registration and the actual presence in the country, tax risks of tax evasion are increasing. The conclusions have been made about the need to identify new emerging economic relations and their legal consolidation, development and implementation of effective tax policy, and on its basis the transformation of the tax system.